CALCULATION, PAYMENT, REPORTING, AND RECORDING OF VALUE ADDED TAX USING THE CORETAX SYSTEM AT PT. EKASAPTA PRIMA MAKMUR - Thania Shaumy Ramadhan (IC-BESTS: International Conference on Business, Economics, Technology, and Social Sciences, 2026)
This study aims to determine the process of calculating, depositing, reporting, and recording Value Added Tax (VAT) as well as the implementation of the Coretax system at PT. Ekasapta Prima Makmur. The research method used is a descriptive method with data collection techniques through observation, interviews, and documentation. The results of the study indicate that the VAT calculation has been carried out in accordance with applicable tax regulations using an 11% VAT rate on the Tax Base (DPP). The process of depositing and reporting VAT is conducted electronically through the Coretax system, starting from input tax crediting to the reporting of the VAT Periodic Tax Return. The implementation of the Coretax system helps the company improve the effectiveness and efficiency of tax administration, although there are still several obstacles in its implementation